URGENSI AKUNTANSI ISLAM DI ERA MODERN - Putri, Juliana (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This paper aims to determine the importance of the Islamic Accounting in modern era. In particular, the paper analyzes the values of the Islamic principles in the accounting process that prevent the unexpected activity such as fraud, dishonest etc to appear in reality. Arthur Anderson case was a result of the fraudulent activities that lead to its termination. Certainly this kind of case is expecting not to be happened in the future. Design/methodology/approach – The paper adopts the descriptive analysis and elaboration of the important element of the Islamic principles used in the accounting process. Furthermore, this paper attempt to make clear distinction between values underlying the Islamic accounting and that of the conventional accounting. Findings the comparison of those two systems leads to the conclusion that the value in Islam such as honest, fair, truth (which is important in the Islamic accounting process) has more meaning than the similar value of in the conventional accounting. Hold firmly the Islamic value obviously leads to the decrease fraudulent practices and other unexpected activities. Moreover, it increases the social welfare of the stakeholders as Islam requests people to bring as much as benefit to other community. Practical implication– The implication is that the current conventional modern accounting value must be redefined to bring the stakeholders in getting more benefit and creating less damage to the society. The reporting value should provide information to the stakeholders on the current state of the real condition and provide solution which leads to the increase of the stakeholders’ welfare. Keywords: Islamic Accounting, Conventional Accounting, Islamic Principle. Abstrak Tulisan ini bertujuan untuk mengetahui pentingnya Akuntansi Islam di era modern. Secara khusus, makalah ini menganalisis nilai-nilai prinsip-prinsip Islam dalam proses akuntansi yang mencegah kegiatan tak terduga seperti penipuan, tidak jujur ​​dll untuk muncul dalam kenyataan. Kasus Arthur Anderson adalah hasil dari kegiatan penipuan yang mengarah pada penghentiannya. Tentu saja kasus seperti ini berharap tidak terjadi di masa depan. Desain / metodologi / pendekatan - Tulisan ini mengadopsi analisis deskriptif dan elaborasi elemen penting dari prinsip-prinsip Islam yang digunakan dalam proses akuntansi. Selanjutnya, tulisan ini berusaha untuk membuat perbedaan yang jelas antara nilai-nilai yang mendasari akuntansi Islam dan akuntansi konvensional. Temuan perbandingan kedua sistem mengarah pada kesimpulan bahwa nilai dalam Islam seperti jujur, adil, kebenaran (yang penting dalam proses akuntansi Islam) memiliki makna lebih dari nilai yang sama dalam akuntansi konvensional. Berpegang teguh pada nilai Islam jelas mengarah pada penurunan praktik penipuan dan kegiatan tak terduga lainnya. Selain itu, ini meningkatkan kesejahteraan sosial para pemangku kepentingan karena Islam meminta orang-orang untuk membawa sebanyak manfaat bagi komunitas lain. Implikasi praktis - Implikasinya adalah bahwa nilai akuntansi modern konvensional saat ini harus didefinisikan ulang untuk membawa para pemangku kepentingan mendapatkan lebih banyak manfaat dan menciptakan lebih sedikit kerusakan pada masyarakat. Nilai pelaporan harus memberikan informasi kepada para pemangku kepentingan tentang kondisi terkini dari kondisi nyata dan memberikan solusi yang mengarah pada peningkatan kesejahteraan para pemangku kepentingan. Kata kunci: Akuntansi Syariah, Akuntansi Konvensional, Prinsip Syariah